2011
DOI: 10.1007/s10803-010-1169-6
|View full text |Cite
|
Sign up to set email alerts
|

Is Neonatal Jaundice Associated with Autism Spectrum Disorders: A Systematic Review

Abstract: Using guidelines of the Meta-analysis of Observational Studies in Epidemiology Group, we systematically reviewed the literature on neonatal jaundice (unconjugated hyperbilirubinemia) and Autism Spectrum Disorder (ASD) in term and preterm infants. Thirteen studies were included in a meta-analysis. Most used retrospective matched case–control designs. There was significant heterogeneity (Q = 31, p = 0.002) and no evidence of publication bias (p = 0.12). Overall, jaundice, assessed by total serum bilirubin (TSB),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 73 publications
(104 reference statements)
6
65
1
1
Order By: Relevance
“…Among 13 studies that were combined in a meta-analysis that suggested a link between jaundice and ASD, only 6 studies controlled for potential confounders, and 5 of these 6 studies were limited by either no TSB values available, jaundice definitions based on birth weight, or recall bias due to the use of parental questionnaires to determine the presence of jaundice. 5 Our findings corroborate several known sociodemographic risk factors for ASD, including advanced parental age and education, male sex, lower gestational age, and low birth weight. 41 -44 After adjusting for confounders such as maternal age and education, the rate of ASD was lower in Asians, African Americans, and Hispanics than in whites.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Among 13 studies that were combined in a meta-analysis that suggested a link between jaundice and ASD, only 6 studies controlled for potential confounders, and 5 of these 6 studies were limited by either no TSB values available, jaundice definitions based on birth weight, or recall bias due to the use of parental questionnaires to determine the presence of jaundice. 5 Our findings corroborate several known sociodemographic risk factors for ASD, including advanced parental age and education, male sex, lower gestational age, and low birth weight. 41 -44 After adjusting for confounders such as maternal age and education, the rate of ASD was lower in Asians, African Americans, and Hispanics than in whites.…”
Section: Discussionsupporting
confidence: 85%
“…Past studies relied on administrative diagnoses or parental report of jaundice instead of analyzing total serum bilirubin (TSB) levels 7 -11 ; evaluated a dichotomous hyperbilirubinemia variable based on traditional cutoffs or infant weight 12 -15 ; did not control for confounding 9,11,16,17 ; were not population-based 9,16,17 ; or included a relatively small sample (N < 120) of children with ASD. 10,16,17 Thus, the heterogeneity (P = .002) 5 and limitations of previous studies limit the conclusions that can be drawn.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study from India showed that prematurity was associated with neonate hyperbilirubinemia in ASD [23], but this association was not found in the meta-analysis [24]. In this retrospective study, we analyzed two different ASD groups and showed that the level of TSB in the neonatal period in the ASD group was higher than in the NBAS is a reliable and useful instrument, and had been used by other studies of prenatal exposure and infant outcomes [31][32][33].…”
Section: And 1998 In Kaiser Permanente Northernmentioning
confidence: 88%